Pengaruh Inflasi, Tingkat SBBI (Suku Bunga Bank Indonesia), FDR (Financing to Deposit Ratio), dan NPF (Non-Performing Financing) Terhadap Penetapan Nisbah Bagi Hasil Deposito (Studi Empiris Pada Perbankan Syariah yang Terdaftar di OJK Periode 2013-2017) - Angga Rianto (ITB AAS INDONESIA Surakarta, 2021)
This study aims to test the relationship between Inflation, SBBI, FDR and NPF levels with the determination of Deposit Revenue Ratio. This research is done by quantitative methods, where research instruments use documentation and surveys. while the population sample is determined through purposive sampling technique. In Statistical Testing in this study using SPSS version 21, with a sample of the population of Islamic banks moving in the field of goods and consumption in BEI in the period 2013 - 2017. A total of 8 Islamic banks out of a total of 12 Islamic banks taken as research sample. Data analysis tools use multiple linear regression analysis. The results of this study show that Inflation, SBBI Level, FDR proved to have a significant influence with the Deposit Revenue Share Ratio. However, the NPF variable shows no effect on the Deposit Revenue Ratio. This study is conducted yet limited only to the Factors influencing the Ratio of Revenue Deposit which is limited to the Inflation, SBBI, FDR, and NPF variables. This research is expected to be a reference in determining the policy on Islamic banks, helping capital owners to be wiser in managing financial instruments and resources, and can be used to increase research insights in the future. Keywords: Inflation, Bank Indonesia Interest Rate, Financing to Deposit Ratio, Non-Performing Financing and Profit-Sharing Ratio. JEL Clasification: E31, E43, G21